Pengaruh Kerjasama Tim dan Motivasi Terhadap Kinerja Karyawan pada Bosscha Space - Hermaela, Amelia Novianti; Kustiwa, Atep (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of Teamwork and Motivation on employee performance at Bosscha Space, both partially and simultaneously. This research method uses quantitative methods with a population of 32 people. Data collection using a questionnaire given to the company. From the results of data processing, it was found that the Teamwork variable (X1), the Motivation variable (X2) and employee performance (Y) were declared valid and reliable for research. After doing the t test, Teamwork has a tcount value of 2.557 and a t table of 2.045 where t count is greater than t table means Teamwork has a partial effect on employee performance. The Motivation variable has a tcount value of 3.396 and a t table of 2.045 where t count is greater than t table means Motivation has a partial effect on employee performance. Based on the results of the F test, the Fcount value of 32.642 is greater than the Ftable of 3.32. Due to the value of Fhitung> Ftabel (32.642> 3.32), H0 is rejected and H3 is accepted, meaning that the Teamwork and Motivation variables simultaneously affect employee performance.